2020
DOI: 10.1371/journal.pone.0241910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physiological changes and social life events on adrenal glucocorticoid activity in female zoo-housed Asian elephants (Elephas maximus)

Abstract: Ensuring good health and welfare is an increasingly important consideration for conservation of endangered species and includes breeding of individuals managed under human care. Understanding how factors in the captive environment affect individual animal wellbeing can be aided by long-term monitoring of biological functioning. This study involved longitudinal assessments (4 to 28 years) of reproductive and adrenal hormones in zoo-housed female Asian elephants (Elephas maximus) (age range 4 to ~71 years) to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 108 publications
2
11
2
Order By: Relevance
“…The continued and regular ovarian cycling observed in females throughout the construction period and transition to the new habitat represents one indicator of normal reproductive health and welfare for the female elephants in this study. In our previous long-term study of gonadal [ 75 ] and adrenal activity [ 102 ] of female Asian elephants, we found that major life events—births, deaths, changes in herd structure—had minimal effect on estrous-cycle dynamics over time and adrenal responses were activated only short-term, suggesting that the Oregon Zoo’s female elephants are quite resilient and maintain normal reproductive and adrenal health. Historically, male elephants at the Oregon Zoo exhibited typical annual musth cycles [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The continued and regular ovarian cycling observed in females throughout the construction period and transition to the new habitat represents one indicator of normal reproductive health and welfare for the female elephants in this study. In our previous long-term study of gonadal [ 75 ] and adrenal activity [ 102 ] of female Asian elephants, we found that major life events—births, deaths, changes in herd structure—had minimal effect on estrous-cycle dynamics over time and adrenal responses were activated only short-term, suggesting that the Oregon Zoo’s female elephants are quite resilient and maintain normal reproductive and adrenal health. Historically, male elephants at the Oregon Zoo exhibited typical annual musth cycles [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jakob-Hoff et al [ 115 ] observed increased vigilance and apprehension in zoo elephants exposed to short periods of construction noise, but construction disturbance occurred over an extended time in the current study, so there was potential for habituation and there was no evidence of any lasting negative effects. Although the females in this study historically have not exhibited signs of chronic stress [ 102 ], Carlstead and Brown [ 116 ] argue that high variability in longitudinal FGM data may be a better measure of increased reactivity than increased mean levels, because the best indicator of chronic stress in animals subjected to intense stressors of long duration or repetitiveness may be more frequent or exaggerated glucocorticoid responses to new and acutely presented stressors (Mason et al, in prep).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, serum concentrations of cortisol are significantly negatively correlated with progesterone during the average 14‐week long estrous cycles in captive African elephants (Bechert et al, 1999). In Asian elephants, no difference in serum cortisol concentrations during the estrous cycle was found (Oliveira et al, 2008); however, a subsequent study with a greater number of Asian elephants did find regular cortisol peaks during the second half of the follicular phase followed by lower levels during the luteal phase (Fanson et al, 2014; Glaeser et al, 2020) similar to African elephants. Progesterone can: (1) increase the rate of dissociation of GCs from receptors by binding GC and mineralocorticoid receptors; (2) modulate the receptor number in the hippocampus; and (3) diminish the effectiveness of cortisol feedback on stress responsiveness (Kudielka & Kirschbaum, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In both elephant species, studies revealed inter-individual variation in GC responses to captive husbandry situations in all sampling matrices (African elephant, blood: [ 21 ], saliva: [ 31 ]; Asian elephant, feces: [ 55 ], blood and urine: [ 56 ]). The individual factors shown to influence GC levels within or between individual elephants include age (African elephant: [ 57 ]; Asian elephant: [ 56 ]), sex (wild African elephant: [ 19 ]), facility [ 23 ], personality (African elephant: [ 29 ]; Asian elephant: [ 55 ]), day time [ 28 , 29 , 58 , 59 , 60 ] and reproductive status or ovarian cycle phase (African and Asian elephant: [ 61 ]; African elephant: [ 62 , 63 ]; Asian elephant: [ 56 , 64 , 65 ]).…”
Section: Introductionmentioning
confidence: 99%